2020
DOI: 10.3390/polym12102399
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Cellulose Nanofiber and Nanoclay as Distributed Phase in a Polypropylene Based Nanocomposite System

Abstract: Since the plastic-based multilayer films applied to food packaging are not recyclable, it is necessary to develop easily recyclable single materials. Herein, polypropylene (PP)-based cellulose nanofiber (CNF)/nanoclay nanocomposites were prepared by melt-mixing using a fixed CNF content of 1 wt %, while the nanoclay content varied from 1 to 5 wt %. The optimum nanoclay content in the PP matrix was found to be 3 wt % (PCN3), while they exhibited synergistic effects as a nucleating agent. PCN3 exhibited the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…It was found that the nanoclay interlayer spacing decreases with the increase in nanoclay content. As the nanoclay content increased, nanoclay agglomeration increased, and the interlayer distance value decreased as the PP chains were too insufficient to effectively penetrate between the nanoclays [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the nanoclay interlayer spacing decreases with the increase in nanoclay content. As the nanoclay content increased, nanoclay agglomeration increased, and the interlayer distance value decreased as the PP chains were too insufficient to effectively penetrate between the nanoclays [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polypropylene (PP) is a good candidate for packaging material due to its advantages, such as having a low cost, a high mechanical strength, excellent moisture barrier properties, easy processability, and a high recyclability [ 4 ]. However, PP has poor oxygen barrier properties, therefore its use in the packaging fields requiring oxygen barrier performance is limited.…”
Section: Introductionmentioning
confidence: 99%
“…While the WVP was reduced slightly from 0.38 ± 0.02 (control) to 0.37 ± 0.02 g.mm/m 2 .day.atm with the addition of 5 wt% nanoclay. Both the polymer and the inclusion of nanoclay showed excellent WVP [ 68 ].…”
Section: Properties Of Nanoclays-containing Bio-based Packaging Mater...mentioning
confidence: 99%
“…Different types of nanoclay, including montmorillonite [ 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ], saponite [ 180 , 185 , 186 ], bentonite [ 187 ], aminoclay [ 188 ], and vermiculite [ 189 ], have been used to fabricate hybrid nanocellulose-based nanocomposites. In some studies, the hybrid nanocomposites were made by adding another component, such as chitosan [ 177 , 190 ] or a polymer [ 191 , 192 , 193 , 194 , 195 , 196 , 197 ].…”
Section: Nanocellulose/nanomaterials Hybrid Polymer Compositesmentioning
confidence: 99%